Supporting college student mental health: A university-wide partnership - Debra L. Franko; Christine Civiletto; Kellianne Carfi; Megan O’Hara (Cogent Mental Health)
In a unique partnership, the Office of Student Life (which oversees counseling and wellness services) joined with the Office of the Provost (which oversees academic programs and faculty) to create a robust response to student mental health concerns by involving faculty in this effort. This approach included written guidelines and comprehensive training for faculty in a multilayered approach. The training program resulted in positive post-workshop responses from faculty who reported greater comfort in dealing with student concerns and increased awareness of resources. Partnerships between the academic side of a university and the student services side can bolster other campus resources to support college student mental health.